THE DYNAMICS OF THE SAUDI—YEMEN CONFLICT: A SOCIAL CONSTRUCTIVIST ANALYSIS OF PUBLIC PERCEPTION - Rista Choirotun Nisa; Khoirun Nisak; Wildana Wargadinata (Arabic Literature Department, 2024)
This study examines the conflict between Saudi Arabia and Yemen, which impacts political, economic, and social aspects. The background of this research is Yemen's internal conflict involving Saudi Arabia's military intervention since 2015. This study analyzes the public's perception of the intervention and its impact. Using the theories of social constructivism by Peter L. Berger and Thomas Luckmann, this study identifies how public perceptions are shaped through narratives constructed by the media, governments, and other social actors. The method used is qualitative with an analytical descriptive approach through the explanation of conflict variables, community conditions, and the impact of the intervention. The discussion results show that public perceptions are divided into positive perceptions that see intervention as an effort for stability in the region and negative perceptions that consider intervention to exacerbate humanitarian and economic crises. Despite the political benefits, the negative impact on civil society is enormous. Therefore, a diplomatic approach that prioritizes human rights and the welfare of civil society, as well as inclusive reconciliation efforts to achieve sustainable peace, is needed.